2014
DOI: 10.5897/jvmah2014.0316
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, cyst viability, organ distributions and financial losses due to hydatidosis in cattle slaughtered at Nekemte municipal abattoir, Western Ethiopia

Abstract: A cross-sectional study was conducted from October, 2013 to March, 2014 to assess the prevalence, cyst viability, organs distribution and direct financial losses of hydatidosis in cattle slaughtered at Nekemte municipal abattoir. Out of 473 inspected cattle at postmortem inspection, 82 (17.34%) were harboring a single or multiple hydatid cysts. Significantly (P < 0.05) higher infection rate was observed in different age groups and body condition scores. Anatomical organ distributions of cysts showed 64.2, 32.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The ndings of the scienti c study were comparable to the prevalence reported by [27] 20% in Debre Makos, 22.4% in Jimma [31], 22.6% in Konso [32], and they were relatively similar ndings of bovine Hydatidosis have also been reported in neighboring countries, Morocco and Kenya, where the prevalence was reported to be 23% [33] and 19.4% [34]. However, [19] was found that a prior report at Nekemte Municipal Abattoir (17.34%) was lower than current study. Furthermore, a lower prevalence of bovine Hydatidosis was observed throughout the country, with 11.26% in Mizan Teppi [35], 11.6% in Mekelle by [36], and 16% in Wolaita Sodo by [37].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The ndings of the scienti c study were comparable to the prevalence reported by [27] 20% in Debre Makos, 22.4% in Jimma [31], 22.6% in Konso [32], and they were relatively similar ndings of bovine Hydatidosis have also been reported in neighboring countries, Morocco and Kenya, where the prevalence was reported to be 23% [33] and 19.4% [34]. However, [19] was found that a prior report at Nekemte Municipal Abattoir (17.34%) was lower than current study. Furthermore, a lower prevalence of bovine Hydatidosis was observed throughout the country, with 11.26% in Mizan Teppi [35], 11.6% in Mekelle by [36], and 16% in Wolaita Sodo by [37].…”
Section: Discussionsupporting
confidence: 83%
“…The formula proposed by [18] was used to determine the total number of animals needed for the investigation. To calculate the sample size with a 95% con dence interval (CI) and 5% required absolute precision, the study uses 17.34% predicted prevalence [19].…”
Section: Sampling Methods and Sampling Size Determinationmentioning
confidence: 99%